2003
DOI: 10.1128/mmbr.67.4.593-656.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Bacterial Outer Membrane Permeability Revisited

Abstract: Gram-negative bacteria characteristically are surrounded by an additional membrane layer, the outer membrane. Although outer membrane components often play important roles in the interaction of symbiotic or pathogenic bacteria with their host organisms, the major role of this membrane must usually be to serve as a permeability barrier to prevent the entry of noxious compounds and at the same time to allow the influx of nutrient molecules. This review summarizes the development in the field since our previous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

81
3,800
5
37

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 3,782 publications
(4,020 citation statements)
references
References 803 publications
81
3,800
5
37
Order By: Relevance
“…EDTA removes stabilizing divalent cations from their binding sites in lipopolysaccharides (LPS) of the OM and this results in the release of a significant proportion of LPS on the cell surface disorganizing the OM (31). It is assumed that consequent migration of glycerophospholipids from the inner leaflet to the outer leaflet of the OM establishes glycerophospholipid bilayer domains, which allow the rapid permeation of lipophilic compounds (36). An optimal OM destabilization requires not only the removal of divalent cations but also a replacement of those and other cations by monovalent organic amines.…”
Section: Fluorogenic Substratesmentioning
confidence: 99%
“…EDTA removes stabilizing divalent cations from their binding sites in lipopolysaccharides (LPS) of the OM and this results in the release of a significant proportion of LPS on the cell surface disorganizing the OM (31). It is assumed that consequent migration of glycerophospholipids from the inner leaflet to the outer leaflet of the OM establishes glycerophospholipid bilayer domains, which allow the rapid permeation of lipophilic compounds (36). An optimal OM destabilization requires not only the removal of divalent cations but also a replacement of those and other cations by monovalent organic amines.…”
Section: Fluorogenic Substratesmentioning
confidence: 99%
“…33 In Gram-negative bacteria the development of resistance to b-lactam antibiotics depends, in addition to the production of lactamase enzymes, on down-regulation of porin expression, or porin functional modification through mutation. [34][35][36] Nonetheless, it has been reported that under antibiotic stress, OmpF was preferentially lost in E. coli K-12, but OmpC was overproduced, and the strain showed resistance to only some b-lactams. 37 In the light of this finding, increasing the antibiotic concentration during recombinant protein expression when ampicillin/carbenicillin resistance is used, might help with reducing the amount of expressed OmpF, but the total porin amount is likely to remain the same.…”
Section: Crystal Packing Of Ompf Prepared In Fc12mentioning
confidence: 99%
“…The permeability to antibiotics -or uptake -is the very first line of defense of Gram-negative bacteria, that are protected by an outer-membrane [1]. In the case of E.coli, the uptake of several classes of β-lactam antibiotics, a prominent group in our current antibacterial arsenal, is largely controlled by general diffusion protein channels such as Outer Membrane Protein F (OmpF) [1].…”
Section: Introductionmentioning
confidence: 99%